Transfer Pricing: A Case Study on PT XX Policy in Related Party Transactions - Kurnadi, Jemmy; Secokusumo, Thomas H. (The Indonesian Journal of Business Administration, 2012)
Transfer pricing has becoming a great fear among companies in Indonesia, especially when Indonesian Tax Office launched its significant initiatives back in 2009 / 2010, where it required companies which submitted their annual tax return to be attached with transfer pricing documentation for company’s related party transactions. Though it has be to admitted that related party transactions mostly used by multinational companies to set up the profit level at the maximum by utilizing different tax regimes of the countries where the companies domiciles. Focus of this final project are maintained on major related party transactions, which are: 1) sales, 2) management and technical assistance fee, 3) charge related to shared services performed by related party domiciled in Malaysia. This is in accordance with tax regulation recently issued in 2011, stating that only transactions > IDR10 billion that required transfer pricing analysis / documentation.The first result of the analysis showed that it will be financially advantageous for the Company to increase the sales price which will affect decrease in global tax expense. However, given the complexities of changing the sales contract with the shareholder, tax implication for Japan business unit, it is advised that the Company maintain its sales price at the current level. The second result is to recommend the Company to revise its transfer pricing method for its MTA fee to a cost based / cost plus method as it would give better rationale of the transaction for Indonesia Tax Office. The third result is to deny the proposal of setting up the shared service organization in Malaysia for Indonesia business unit as it is financially inefficient and making further complexity on the tax administration in Indonesia. Keywords: transfer price, related party transactions, transfer pricing, arm’s length transaction